Efficacy of Posaconazole Prophylaxis for Fungal Disease in Hematology Patients Treated With Chemotherapy and Transplantation: An Open-Label, Prospective, Observational Study - Li, Weiyang; Xia, Fan; Zhou, Haixia; Qiu, Huiying; Wu, Depei; Ma, Xiao; Sun, Aining (Frontiers in Microbiology, 2020)
Background Posaconazole (PCZ) is used prophylactically to prevent invasive fungal infections (IFIs) in patients with hematological malignancies. Objective To evaluate the cut-off serum concentration of PCZ for successful IFI prophylaxis in Chinese subjects. Patients and Methods A total of 74 patients treated with induction chemotherapy (n = 10) and allogeneic hematopoietic stem cell transplantation (HSCT) (n = 64), who received PCZ prophylactically as an oral suspension for >7 days, were included in the study. Clinical, radiological, microbiological culture results, and treatment responses were analyzed and drug concentration assays performed. Results The overall incidence of possible, probable, and proven IFIs was 13.5% (10/74), with five patients in the chemotherapy group and five in the HSCT group. The PCZ serum concentration in most patients (54/63) was in the range of 0.25–1.0 μg/ml, and this concentration range was significantly associated with the success rate of PCZ prophylaxis. A cut-off value of 0.47 μg/ml can be considered as an evaluation index for PCZ prophylaxis. Taking a proton pump inhibitor (PPI) would reduce the PCZ blood concentration, but not affect the IFD breakthrough point. PCZ treatment for hematopoietic malignancy or HSCT patients with a serum concentration of PCZ < 0.47 μg/ml were risk factors for PCZ prophylaxis of IFIs, determined by univariable and multivariable regression analyses. Conclusion The serum concentration of PCZ was related to the incidence of IFIs and a serum concentration of >0.47 μg/ml is highly recommended to avoid IFIs after chemotherapy or HSCT. Clinical Trial Registration Chinese Clinical Trial Registry: ChiCTR1900026294.